Pyoluteorin and 2,4-diacetylphloroglucinol are major contributors to Pseudomonas protegens Pf-5 biocontrol against Botrytis cinerea in cannabis - Balthazar, Carole; St-Onge, Renée; Léger, Geneviève; Lamarre, Simon G.; Joly, David L.; Filion, Martin (Frontiers in Microbiology, 2022)
Pseudomonas protegens Pf-5 is an effective biocontrol agent that protects many crops against pathogens, including the fungal pathogen Botrytis cinerea causing gray mold disease in Cannabis sativa crops. Previous studies have demonstrated the important role of antibiotics pyoluteorin (PLT) and 2,4-diacetylphloroglucinol (DAPG) in Pf-5-mediated biocontrol. To assess the potential involvement of PLT and DAPG in the biocontrol exerted by Pf-5 against B. cinerea in the phyllosphere of C. sativa, two knockout Pf-5 mutants were generated by in-frame deletion of genes pltD or phlA, required for the synthesis of PLT or DAPG respectively, using a two-step allelic exchange method. Additionally, two complemented mutants were constructed by introducing a multicopy plasmid carrying the deleted gene into each deletion mutant. In vitro confrontation assays revealed that deletion mutant ∆pltD inhibited B. cinerea growth significantly less than wild-type Pf-5, supporting antifungal activity of PLT. However, deletion mutant ∆phlA inhibited mycelial growth significantly more than the wild-type, hypothetically due to a co-regulation of PLT and DAPG biosynthesis pathways. Both complemented mutants recovered in vitro inhibition levels similar to that of the wild-type. In subsequent growth chamber inoculation trials, characterization of gray mold disease symptoms on infected cannabis plants revealed that both ∆pltD and ∆phlA significantly lost a part of their biocontrol capabilities, achieving only 10% and 19% disease reduction respectively, compared to 40% achieved by inoculation with the wild-type. Finally, both complemented mutants recovered biocontrol capabilities in planta similar to that of the wild-type. These results indicate that intact biosynthesis pathways for production of PLT and DAPG are required for the optimal antagonistic activity of P. protegens Pf-5 against B. cinerea in the cannabis phyllosphere.